Gene expression of ceramide metabolism enzymes in fat depots of different localization in cardiovascular diseases - O. V. Gruzdeva; E. V. Belik; Yu. A. Dyleva; E. G. Uchasova; A. V. Ponasenko; A. G. Kutikhin; V. E. Markova; E. E. Gorbatovskaya; E. V. Fanaskova; S. V. Ivanov; A. N. Stasev; M. G. Zinets; et al. (Российский кардиологический журнал, 2023)
Aim. To assess gene expression of enzymes of the sphingomyelinase pathway of ceramide biosynthesis and degradation in fat depots of various localization in patients with cardiovascular diseases.Material and methods. A total of 38 patients were examined: 20 with coronary artery disease (CAD) and 18 with aortic stenosis/insufficiency. Biopsies of subcutaneous, epicardial, perivascular adipose tissue (AT) (SAT, EAT, PVAT, respectively) were obtained during surgery. The gene expression of sphingomyelinase pathway enzymes (acid and neutral sphingomyelinase SMPD1 and SMPD3) and the degradation of ceramides (acid ceramidase ASAH1; sphingomyelin synthase 1 and 2 SGMS1 and SGMS2) was assessed using a quantitative polymerase chain reaction. Analysis of the level of corresponding proteins was carried out using immunoblotting (western blotting). Statistical processing was performed using GraphPad Prism 8 (GraphPad Software).Results. In CAD, the maximum expression of SMPD1 was observed in subcutaneous and epicardial adipocytes. In acquired heart defects (AHD), the level of SMPD1 mRNA in the SAT was higher than in the PVAT. Expression of the SMPD1 gene in the EAT of patients with CAD was more pronounced than in patients with heart defects. PVAT was characterized by minimal expression of SMPD1 regardless of disease. Expression of SMPD3 had no tissue features in studied groups, while SMPD1 was more expressed in cardiac AT adipocytes than SMPD3. ASAH1 in the EAT of patients with CAD was maximal relative to adipocytes of other localizations. Persons with AHD were characterized by a high expression of ASAH1, regardless of AT localization, exceeding the values of patients with CAD. In CAD, the level of SGMS1 in EAT was higher than in SAT and PVAT, while no differences were found in patients with AHD depending on AT location. SGMS1 gene expression in EAT of patients with CAD was higher than in the group of AHD. Expression of SGMS2 significantly exceeded SGMS1 in both study groups and was maximal in SAT and PVAT adipocytes compared to EAT in the CAD group and in PVAT in the AHD group. Coronary pathology was characterized by a higher level of SGMS2 mRNA in SAT and EAT. The level of ceramide metabolism enzymes in AT of patients corresponded to the expression of their genes.Conclusion. In coronarogenic disease, cardiac AT (mainly epicardial) is characterized not only by increased expression of gene ceramide synthesis enzymes via the sphingomyelinase pathway, but also by activation of ceramide utilization with sphingosine formation. The observed changes may contribute to the accumulation of ceramides and sphingomyelin associated with atherosclerotic processes.